2016
DOI: 10.14238/sp10.1.2008.34-41
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Antibiotik Secara Bijak Untuk Mengurangi Resistensi Antibiotik, Studi Intervensi di Bagian Kesehatan Anak RS Dr. Kariadi

Abstract: Latar belakang. Masalah resistensi antibiotik di Indonesia sudah mengkhawatirkan. Penggunaan antibiotiksecara bijak merupakan kunci utama pengendalian resistensi.Tujuan. Penelitian bertujuan meneliti faktor-faktor yang mempengaruhi kualitas penggunaan antibiotikdi Bangsal Kesehatan Anak RS Dr. Kariadi dan menguji apakah kualitas dapat ditingkatkan denganpelatihan.Metode. One group pretest and post test subjek adalah 22 dokter yang merawat pasien kelas III, mengikutipelatihan penggunaan antibiotik, dan dapat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
3
Order By: Relevance
“…A total of 13 reports reported data on the effect of AMS interventions, of which 11 in hospitals, 23,28,31,33,47,[86][87][88][89][90][91] 1 in primary care, 92 and 1 in community pharmacies 93 (Table 2). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 reports reported data on the effect of AMS interventions, of which 11 in hospitals, 23,28,31,33,47,[86][87][88][89][90][91] 1 in primary care, 92 and 1 in community pharmacies 93 (Table 2). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
“…23,31,47,86,88,90,91 Studies that evaluated education and/or training interventions (5 reports) reported mixed effects on antibiotic consumption and prescribing appropriateness. 31,[87][88][89]92 The one study that evaluated antibiotic restriction with pre-approval found that consumption of restricted antibiotics decreased and of unrestricted narrow-spectrum antibiotics increased. 28 The one randomised study that evaluated the effect of a pharmacist counselling session of outpatient antibiotic users in community pharmacies found that self-reported antibiotic adherence was 311 significantly higher in the intervention group compared to the control group.…”
Section: Antibiotic Stewardship Interventionsmentioning
confidence: 99%
“…Di sisi lain, dampak dari resistensi bakteri ini ialah kegagalan dalam pengobatan penyakit dengan terapi antibiotik. Hal ini tentunya akan sangat merugikan dan berampak buruk bagi kesehatan masyarakat di masa depan (Farida, et. al., 2016).…”
Section: Gambar 2 Proses Diskusi Teararah (Fgd)unclassified
“…This should not occur in inpatients who can be monitored 24 hours and the availability of a more complete diagnostic tool. 17 National health insurance services are carried out by conducting cooperation agreements between BPJS and health facilities that exist throughout Indonesia. 20 Analysis of antibiotic financing in hospitals has an effect on the duration of administration of drugs, the amount of drug administration, profit margins, services.…”
Section: Conclussionmentioning
confidence: 99%